Design and development of tension - emitter - JISHITHA RAVINDRAN; Er. Vishnu B (Guide) (Tavanur 2012 DEPARTMENT OF LAND &WATER RESOURCES AND CONSERVATION ENGINEERING)
Design and development of tension - emitter
Design and development of tension - emitter